Formulating design research questions: A framework - Goldschmidt, Gabriela; Matthews, Ben (Design studies, 2022)
This research note addresses the formulation of questions in design research. On the premise that well formulated research questions have far-reaching implications for other aspects of the development and impact of research, articulating quality research questions is an issue of the highest concern. In this note we propose a framework for the formulation of research questions, adapted from clinical research and tailored to empirical design research. The framework, RIN. AFE, pertains to criteria for effective research questions: on the substance side, Relevant, Interesting and Novel; on the methodological execution side, Appropriate, Feasible and Ethical. The application of this framework is demonstrated through an analysis of an award-winning Design Studies paper. • We propose a set of six characteristics of research questions.• Effective empirical design research questions are relevant, interesting, and novel.• Further characteristics pertain to method: appropriate, feasible and ethical.• Research questions have implications for other dimensions of the study.• Quality questions open new lines of inquiry for the field.